Drug Repurposing in the Modern Era: Focus on Newly Approved and Investigational Therapeutic Applications - Varadagolla Spandana; Achutha Giridhar; Yadala Prapurna Chandra (International Journal of Allied Medical Sciences and Clinical Research, 2025)
Drug repurposing has emerged as a pivotal strategy in modern therapeutics, offering cost-effective and accelerated pathways to identify new indications for existing drugs. In the post-genomic era, the field has shifted from serendipitous observations to data-driven, mechanism-guided repositioning, leveraging computational intelligence, multi-omics integration, and network pharmacology. Advances in artificial intelligence, machine learning, and CRISPR-based functional genomics have enabled systematic identification of drug–disease interactions, while translational approaches including adaptive clinical trials and biomarker-guided patient stratification ensure rapid validation and clinical applicability. Recent successes, such as the repurposing of remdesivir for COVID-19, ketamine/esketamine for treatment-resistant depression, and colchicine for cardiovascular inflammation, underscore the impact of these strategies. Emerging pipelines targeting oncology, neurodegenerative diseases, and regenerative medicine highlight the potential of repurposing to address unmet medical needs, including rare and orphan diseases. This review synthesizes the current landscape of drug repurposing, emphasizing novel mechanisms, AI-guided discovery, and translational outcomes, and outlines future directions for sustainable, patient-centered innovation in therapeutics.